Affirmative Action on Women Education and Access of Employment Opportunities by Women in Northern Division Kabale Municipality. - Nasasira, Praise (Kabale University, 2024)
The study examined affirmative action on women's education and access to employment opportunities by women in Northern Division Kabale Municipality. The objectives of the study were; to identify the role of affirmative action on women's education and access to employment opportunities, to examine the causes of gender disparity in education and employment opportunities, and to establish the possible measures to curb the causes of gender disparity in education and employment opportunities. A descriptive research design was used and data was collected using interviews and questionnaires. The study results on the roles of affirmative action on women's education and access to employment opportunities, the highest number of respondents mentioned that affirmative action helps in ensuring a more balanced gender representation and promotes gender sensitivity among all students, and the least number of respondents mentioned that affirmative action initiatives help women to navigate academic challenges and prepare for professional success. The study findings on the causes of gender disparity in education and employment opportunities, the highest number of respondents mentioned a lack of school gender-friendly facilities to provide a favorable environment for students and the least number of respondents mentioned that lack of female teachers as role models is a key factor hindering girls experience quality education. The study findings on the possible measures to curb the causes of gender disparity in education and employment opportunities, the highest number of respondents mentioned that there should be a change of negative socio-cultural beliefs, norms, values, attitudes, and practices collectively about gender disparity in education and the least number of respondents mentioned that there should be promotion of women right by reducing violence against women and girl child to access education. The study recommended that there should be development and promotion of scholarships specifically for women, particularly in fields where they are underrepresented by establishing grants, bursaries, or low-interest loans to support women from economically disadvantaged backgrounds to pursue education at all levels.